2000
DOI: 10.1074/jbc.275.7.4541
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Human T Lymphocytes Is Inhibited by Peroxisome Proliferator-activated Receptor γ (PPARγ) Agonists

Abstract: T lymphocyte activation is highlighted by the induction of interleukin-2 (IL-2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
279
0
3

Year Published

2000
2000
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 368 publications
(292 citation statements)
references
References 17 publications
10
279
0
3
Order By: Relevance
“…Moreover, administration of PPAR␥ ligands is reported to attenuate inflammation in murine models of inflammatory bowel disease (18), nonobese diabetic mice (19), rodent models of atherosclerosis (20 -22) and experimental allergic encephalomyelitis (EAE) (23,24). Studies performed in lymphocyte subpopulations have also confirmed the anti-inflammatory actions of the PPAR ligands (11,25).…”
mentioning
confidence: 70%
“…Moreover, administration of PPAR␥ ligands is reported to attenuate inflammation in murine models of inflammatory bowel disease (18), nonobese diabetic mice (19), rodent models of atherosclerosis (20 -22) and experimental allergic encephalomyelitis (EAE) (23,24). Studies performed in lymphocyte subpopulations have also confirmed the anti-inflammatory actions of the PPAR ligands (11,25).…”
mentioning
confidence: 70%
“…PPAR expression changes with T-cell activation and proliferation following T-cell receptor (TCR) stimulation. Interestingly, PPARγ negatively regulates T-cell activation following TCR stimulation by inhibiting nuclear factor of activated T-cells (NFAT) and subsequent IL-2 production (Clark et al, 2000;Yang et al, 2000). Treatment of mouse T cells with 15d-PGJ2 or ciglitazone inhibited IL-2 production induced by CD3 stimulation (Clark et al, 2000).…”
Section: Ppars In T Cells and Autoimmunitymentioning
confidence: 99%
“…Treatment of mouse T cells with 15d-PGJ2 or ciglitazone inhibited IL-2 production induced by CD3 stimulation (Clark et al, 2000). Likewise, human T cells showed reduced IL-2 production and proliferation upon phytohaemaglutinin (PHA) stimulation in the presence of these PPARγ ligands (Yang et al, 2000). Rosiglitazone treatment of mouse splenocytes decreased phorbol 12-myristate 13-acetate (PMA) and ionomycin-induced interferon-gamma (IFN-γ) production.…”
Section: Ppars In T Cells and Autoimmunitymentioning
confidence: 99%
“…Upon ligand binding, PPAR␥ heterodimerizes with the retinoid X receptor and binds to PPAR response elements located in the promoter region of target genes. Additionally, important antiinflammatory effects of PPAR␥ are mediated by negative interference with proinflammatory cell signaling, either via competition for coactivators or via transrepression through physical interaction with proinflammatory transcription factors, in particular NF-B (9,10). PPAR␥ agonists include endogenous ligands such as polyunsaturated fatty acids and prostanoids like the PGD 2 metabolite 15-deoxy-⌬ (11, 12) PGJ 2 , as well as several synthetic ligands such as the antidiabetic thiazolidinediones, e.g., pioglitazone (PIO) and rosiglitazone, which are currently being used for the correction of metabolic disturbances in type II diabetes (13).…”
mentioning
confidence: 99%